Influence of Perceived Value and Personal Values on Consumers Repurchase Intention of Natural Beauty Product - Siti Nor Bayaah Binti Ahmad; Azizah Omar (International Journal of Supply Chain Management, 2018)
Consumers concern on health and environment has been remarkable increasing recently. With vaguer product status especially on its impact on human body and health, consumers shifted to a more health option in which products that were produced from natural ingredients. Understanding the consumers concern for their health and wellbeing should be the guideline for marketers in strategizing the marketing tactics. Besides the growing emphasis on external appearance, consumers concerned on health and the environment has appeared as a recent consumer drives. This study aims to investigate the consumers perspective in relation to consumers perceived value and personal values when it comes to their decision to repurchase the same brand of natural beauty products. 300 questionnaires were distributed among the users of natural skin care products with 226 were returned and usable. The study findings indicated that functional value contributed the highest with = 0.398 and p = 0.00, followed by environment consciousness, with = 0.293 and p = 0.000 and health consciousness = 0.264 and p = 0.00. Practically, the findings helped marketers to be creative when promoting the beauty products by emphasizing on ecological beauty or product safety to feed into the womens attitude toward natural beauty products. Having a thoughtful mind on the factors that driven the intention of these women consumers will aid in designing a message with better persuasion.